Estudo do processo de eletrodeposição e caracterização de ligas de Sn-Zn - Taguchi, Allan da Silva (2009)
This study evaluated the electrodeposition processes of Sn, Zn and Sn-Zn alloy in the absence and presence of tartaric acid as complexing agent. Initially all the systems studied were evaluated by Cyclic Voltammetry to determine the deposition potentials of the pure metals and alloy. The results showed that the presence of the complexant shifts the deposition process of both Sn and Zn to more negative potential values. The metals codeposition can be determined by the variation in the shape and potentials of the peaks of deposition in the voltammograms obtained for the alloy when compared to those for individual metals. The potential-step technique (Chronoamperometry) was used to characterize the initial stages of electrocrystallization. It was found that the nucleation processes of Sn (in the absence and presence of the complexant) and Sn-Zn alloy (in complexed medium) are governed by progressive nucleation, while for Zn in both media and for the Sn-Zn alloy in non-complexed medium were ill-defined. Thus, these can be characterized as mixed processes. Films obtained at different deposition potentials were characterized by Scanning Electron Microscopy (SEM), Energy-Dispersive X-Ray Spectroscopy (EDX). It was observed that using the tartaric acid it was possible to obtain more uniform and homogeneous deposits and, apparently, favouring the reduction process and achieving a more protective coating. The morphology, composition and X-Ray Diffraction (XRD) of films galvanostatically deposited varying the complexing agent (potassium sodium tartrate or sodium gluconate) and the deposition current (5,0 mA cm-2 and 30,0 mA cm-2) were also analyzed. It was found that at a lower current density the films obtained showed a better uniformity, while those obtained at a higher current density showed a finer grain structure due to an increased nucleation rate in this last instance. Moreover, we can say that the tartrate favours the deposition of Zn when compared to the gluconate. By the XRD analysis it was possible to observe that the alloys consist of separated phases of Sn and Zn crystals and they do not form any intermetallic compound.